Paths to higher office: Evidence from the Swedish civil service - Klaus J. Brösamle; Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2011)
The paper analyzes the relationship between career path characteristics of civil servants and their career success. Following a description of the institutional setting and some qualitative evidence on typical paths to the top, we use data that follows the careers of all Swedish civil servants for up to 24 years to document a clear link between early mobility and later success. Controlling for a wide range of other factors, incidents of inter-organizational mobility within the administration, but also interchanges between the administrative and other sectors are positively associated with becoming a senior government offcial. We also show that the positive association between mobility and future success is smaller for more educated workers, which is consistent with signalling e ffects driving the link between mobility and career success.
Keywords: J45; J62; M51; 330; public sector employment; job mobility; internal labour markets; signalling; promotions; Swedish civil service; Beamte; Erwerbsverlauf; Arbeitsmobilität; Interner Arbeitsmarkt; Schweden